QR Code-Practicum Guide Based on Guided Inquiry as The Novel Biology Lab Activities Learning Assisted - Mufti Hatur Rahmah; Nurhidayah Nurhidayah; Nurmadina Nurmadina (Jurnal Penelitian Pendidikan IPA, 2023)
Educators play an important role in developing learning tools that are interesting and by the needs of students. This aims to develop a QR Code-Practical Guide based on Guided Inquiry for Class XII MIPA at the High School Level on growth and development in plants and photosynthesis and to determine the validity, practicality, and effectiveness. This type of research is Research and Development with the ADDIE model which consists of 5 stages, namely Analyze, design, development, Implementation, and evaluation. The research location is at SMAN 2 Majene, East Banggae District, Majene Regency, West Sulawesi Province. The research subjects were class XI MIPA 5 which consisted of 31 students. The results of the validation of the QR Code Practical Guide based on Guided Inquiry using the assessment sheet of media experts and material experts who were assessed by 2 expert validators obtained a result of 3.8 which is included in the valid category. The results of the practicality of the QR Code Practical Guide based on Guided Inquiry using teacher response questionnaires and student response questionnaires. The results of the questionnaire analysis show that the value of the teacher's response is 92.6%, getting the very practical category and the value of the student's response is 86.6% getting the very practical category. The results of the QR Code Practical Guide based on Guided Inquiry using test questions, the learning outcomes obtained are 80.7% in the effective category. Thus the QR Code Practical Guide based on Guided Inquiry is declared valid, practical, and effective to be used as teaching materials.